1968
DOI: 10.1139/b68-088
|View full text |Cite
|
Sign up to set email alerts
|

Some neutral constituents of the Rhodophyceae with special reference to the occurrence of the floridosides

Abstract: Isofloridoside, in addition to floridoside, was demonstrated as a constituent of 16 species of the Bangiophycidae and Florideophycidae (Rhodophyceae). Photosynthetic experiments with Porphyra umbilicalis resulted in a very slow labelling of isofloridoside both in light and in darkness after photosynthesis in 14CO2. This observation supports the concept that the floridosides are not equivalent as metabolites.Trehalose was identified as a constituent of species of the Corallinaceae. A dideoxyinositol, D-(+)-14/2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1978
1978
2006
2006

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 9 publications
2
16
0
Order By: Relevance
“…Ia). Craigie et al (1968) carried out I4C photofixation studies on selected red algae, showing that D/L isofloridosides are more weakly 14C-labelled than floridoside. They concluded that floridoside was the primary photoassimilatory product, while D/L isofloridosides are formed from floridoside by a slow isomerisation process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ia). Craigie et al (1968) carried out I4C photofixation studies on selected red algae, showing that D/L isofloridosides are more weakly 14C-labelled than floridoside. They concluded that floridoside was the primary photoassimilatory product, while D/L isofloridosides are formed from floridoside by a slow isomerisation process.…”
Section: Discussionmentioning
confidence: 99%
“…involving D and L forlns of glycerol) and that the two isofloridosides and floridoside may have different physiological roles within this alga, since L-isofloridoside appears to be involved in osmotic adjustment. It would be interesting to investigate the dynamics of mannitol and altritoi I3C tracer exchange in plants of H. elongala maintained in darkness, since similar radiocarbon experiments in red algae suggest that tracer may be transferred very slowly from floridoside to D/L isofloridosides under such conditions (Craigie et al, 1968), confirming that these heterosides are not physiologically and metabolically equivalent, despite their similar structure.…”
Section: Discussionmentioning
confidence: 99%
“…Craigie and McLachlan (1964) showed that glycerol accumulated in the marine green alga Dunaliella tertiolecta photosynthesizing under salinity stress. Photosynthetic products reported included a suite of galactosyl glycerols in red algae (Majak et al 1966;Craigie et al 1968), unusual cyclitols in red algae and chrysophytes (Ramanathan et al 1966;Craigie 1969Craigie , 1974Laycock and Craigie 1970;Craigie et al 1971) and mannitol in prasinophycean and chrysophycean algae . The effects of carboxylic acids on growth and photosynthesis of Haematococcus pluvialis was reported by McLachlan and Craigie (1965) as was photosynthesis in algae containing chlorophyll b (McLachlan and Craigie 1967).…”
Section: Ralph Lewinmentioning
confidence: 99%
“…A novel c-mannoside derivative of floridoside was isolated from this alga by Lindberg (1954), notwithstanding Ross's (1953) claim that mannose is absent. Small quantities of isofloridoside were reported by Craigie et al (1968).…”
Section: Low-molecular-weight Carbohydratesmentioning
confidence: 99%